Lydia, its Land and History - Borsay, Laszlo Aaron
Ph.D.; University Microfilms Order No. 66-8104. Microfilm $3.00; Xerography $6.80; Dissertation Abstracts 27/3 (Ann Arbor, Mich., September 1966) 718A-719A.